Entanglement and coherence in a spin-s XXZ system under non-uniform fields - Ríos, E. (2017)
We investigate entanglement and coherence in an XXZ spin s pair immersed in a non-uniform transverse magnetic field. The ground state and thermal entanglement phase diagrams are analyzed in detail in both the ferromagnetic and antiferromagnetic cases. It is shown that a non-uniform field can control the energy levels and the entanglement of the corresponding eigenstates, making it possible to entangle the system for any value of the exchange couplings, both at zero and finite temperatures. Moreover, the limit temperature for entanglement is shown to depend only on the difference between |h1 - h2| the fields applied at each spin, leading T > 0 for to a separability stripe in the (h1, h2) field plane such that the system becomes entangled above a threshold value of |h1 - h2|. These results are demonstrated to be rigorously valid for any spin s. On the other hand, the relative entropy of coherence in the standard basis, which coincides with the ground state entanglement entropy at T = 0 for any s, becomes non-zero for any value of the fields at T > 0, decreasing uniformly for sufficiently high T. A special critical point arising at T = 0 for non-uniform fields in the ferromagnetic case is also discussed.